Factors associated with retention and adherence on Pre-Exposure Prophylaxis among men who have sex with men in Kigali, Rwanda. - Sezi Mubezi; Samuel S Malamba; Gallican N Rwibasira; Jeanne Uwineza; Jean de Dieu Kayisinga; Eric Remera; Basile Ikuzo; Emah Ndengo; Nadege Umuhoza; Beata Sangwayire; Richard C N Mwesigwa; Caroline E Stamatakis; et al. (PLOS Global Public Health, 2024)
Pre-Exposure Prophylaxis (PrEP) is recommended as an HIV prevention measure for men who have sex with men (MSM). We assessed factors associated with PrEP retention and adherence among MSM in Kigali, Rwanda. We undertook a retrospective cross-sectional study and used a questionnaire to obtain PrEP retention and adherence history from MSM enrolled in the key population (KP) program that attended scheduled follow-up clinics from four (4) health facilities between April 2021 to June 2021. Retention was defined as attending scheduled PrEP follow-up appointments and adherence as taking PrEP medication 95% or more of the time. We used multivariable cox proportion hazard regression to determine factors associated with 3-month retention and principal component analysis (PCA) to determine factors associated with self-reported adherence. Data were analyzed using STATA (version 16.0). We interviewed 439 MSM aged 18 years and above that were initiated on PrEP. Majority were employed (57%, n = 251), between ages 25-34 years (49%, n = 217), close to half completed primary level education (47%, n = 206), were involved in sex work (42%, n = 184), and over a half lived in household of 1-2 members (55%, n = 241). Ninety percent of the MSM respondents (n = 393) were retained on PrEP at 3 months and among those retained, 287 (73%) had good adherence. Multivariable cox regression revealed that MSM more likely to be retained on PrEP, were those that are sex workers (adjusted Hazard Ratio (aHR) = 4.139; 95% Confidence Interval (95%CI): 1.569, 10.921), had more than one (1) regular sexual partners (aHR = 3.949; 95%CI: 2.221, 7.022), lived in households of 3-5 members (aHR = 3.755; 95%CI: 1.706, 8.261), completed secondary school education (aHR = 2.154; 95%CI: 1.130, 4.108), and were circumcised (aHR = 2.218, 95%CI: 1.232, 3.993). Employed MSM had a 66% decreased likelihood to be retained on PrEP (aHR = 0.345; 95%CI: 0.168, 0.707). Similarly, MSM that used condoms consistently had an 85% decreased likelihood to be retained on PrEP (aHR = 0.149; 95%CI: 0.035, 0.632). Principal component regression analysis showed that the component with MSM with higher numbers of regular sexual partners had increased odds of adhering to PrEP (Crude Odds Ratio (cOR) = 1.32; 95%CI: 1.144, 1.530). The study highlighted that MSM using PrEP as the main method of HIV prevention were more likely to be retained and adherent to PrEP. There is need to emphasize PrEP use alongside other HIV prevention methods and targeted STI testing and treatment among PrEP users.